Integrating Islamic Values into Inclusive Curriculum Development in Indonesian Madrasahs and Islamic Boarding Schools - Triana , Mita Anis; Laila, Hapni; Nabilla, Nur Assyifa (Interdisciplinary Journal of Social Sciences, 2025)
Inclusive education is a crucial global issue to ensure equal learning rights for all children, including people with disabilities. In Indonesia, especially in the context of Islamic education, the integration of Islamic values into an inclusive curriculum still faces challenges, such as limited teacher training and suboptimal curriculum design. This study aims to identify and analyze inclusive curriculum models in Islamic educational institutions based on Islamic values. This study was conducted using a systematic literature review method of 24 scientific articles published between 2020 and 2025. The results of the analysis show that the application of Islamic values such as at-ta'aruf (knowing each other), at-tasammuh (tolerance), at-tawassuth (moderation), and at-ta'awun (cooperation) can strengthen an inclusive curriculum. Teachers play a key role in adapting learning to the needs of students and collaborating with parents and communities. Curriculum adaptation and the use of technology also support the creation of a fair and friendly learning environment for all students. This study contributes to the development of a more responsive Islamic education curriculum and serves as a practical reference for policymakers and practitioners in designing inclusive and contextual learning systems.